(untitled) (Fiep Bulletin - online, 2011)
The main goal of this study it was to identify the somatotype profile of the corporal density of the naval school candidates during the years of formation. The population of the candidates is 821. The first sample has 82 candidates, male gender, random selected, being, 24 from 1st grade, 21 from 2nd grade, 20 from 3rd grade and 17 from 4th grade ( about 10%/ year), range ages between 18 and 25 years old, median of 21,37 +- 1,41. Was collected information about age, weight, height, cutaneous folds, perimeters and diameters. For the somatotype calculation was used the heath and Carter (1990), anthropometry method. To calculate the fat percentual (%G), it used the Jackson and Pollock protocol (1993), three folds, correlated to Siri equation (1961). The measure was obtained from the right side, according ISAK of Norton and Olds (2000) recommendations. The statistical treatment was through descriptive analyzes, according to the Costa Neto (1995), with the main purpose was to obtain the profile of the data set, through measure of localization (medium) and dispersion (shunting line- standard) . It admitted the level of significance of p<0, 05, and correlation index (r=0,097). Had been found the followings results for endomorphyc, mesomorphyc and ectomorphic components 1st year= 2,0 – 4,9 – 2,0; 2nd year= 2,3 – 4,4 – 2,0; 3rd year= 2,4 – 4,6 – 1,9; e 4th year= 2,4 – 5,1 – 1,6, respectively. The somatotype profile of 4th and 3rd grades was classified like meso-endomorphyc. And 2nd and 1st grades as balanced mesomorphyc. The fat percentage found was 1st year= 9, 8%, 2nd year= 12, 5%, 3rd year= 12, 5%, 4th year= 15, 8%, being classified as 1st grade = good, 2nd and 3rd grades = medium, average and 4th grade = below average expectations. According to the results we can observe an increase, as much in the somatotype profile, as much in the fat percentage, of the candidates in relation to the years of formation.